Treatment outcomes and patient satisfaction of a virtual partial hospital program: A mixed-method study. (17th February 2023) - Hudson, Chloe C.; Klein, Keith P.; Ong, Clarissa W.; Handy, Ariel B.; Swee, Michaela B.; Lambert, Hilary K.; Mei, Sara; Hom, Melanie A.; Weiss, Rachel B.; Beard, Courtney; Björgvinsson, Thröstur
ABSTRACT: Objective: Despite a proliferation of virtual partial hospital programs (PHP) during the COVID-19 pandemic, there is a dearth of research on such programs. In the current study, we compared treatment outcomes and patient satisfaction between an in-person and a virtual PHP. Further, we examined patients' qualitative feedback about the virtual PHP. Method: Participants included 282 patients attending a virtual PHP during the COVID-19 pandemic and 470 patients attending an in-person PHP one year prior. Patients completed daily measures of symptom severity, and post-treatment measures of patient satisfaction and treatment outcomes. Patients in the virtual PHP provided feedback about virtual care. Quantitative data were analyzed using multilevel modeling, and qualitative data were analyzed using the principles of inductive analysis. Results: Patients experienced a reduction in depression ( b = -.28, p < .001) and anxiety symptoms ( b = -.25, p < .001) over time and reported high satisfaction in both the in-person and virtual PHPs. There were no significant differences across programs. Virtual PHP patients identified unique advantages and disadvantages of virtual care. Conclusion: Our results suggest that virtual PHPs should be explored as an ongoing model of care that may help to systematically reduce barriers to accessing mental health services.